SimICT: a fast and flexible framework for performance and power evaluation of large-scale architecture - Ye, Xiaochun; Fan, Dongrui; Sun, Ninghui; Tang, Shibin; Zhang, Mingzhe; Zhang, Hao (Proceedings of the 2013 International Symposium on Low Power Electronics and Design, 2013)
Simulation is an important method to evaluate future computer systems. However, the increasing complexity of the target systems has made the development of simulators very difficult. Furthermore, detailed simulation of large-scale parallel architecture is so slow that full evaluation of real application becomes a great challenge. This paper presents SimICT, a fast and flexible simulation framework which aims at performance and power evaluation for large-scale architecture. SimICT uses component-based design to improve its flexibility of building target systems. It also introduces an automatic parallel mechanism with relaxed synchronization to speed up the simulation. Finally, it provides a graphic configuration interface to ease the use difficulty. Based on this framework, various existing models, such as performance and power modeling tools, can be integrated to produce a holistic simulation platform.